Peningkatan Pengetahuan tentang Pernikahan Dini Melalui Kegiatan Sosialisasi pada Siswa SMA Negeri 8 Muara Jambi - Netti Herawati; Nuraidah Nuraidah (Universitas Baiturrahim, 2026)
Early marriage remains a serious issue among adolescents and has significant impacts on physical health, psychological well-being, and educational sustainability. Adolescents who marry at a young age are at higher risk of pregnancy complications, maternal mortality, and psychological immaturity, which may lead to household conflict, domestic violence, and divorce. Therefore, improving adolescents’ knowledge regarding the impacts of early marriage is an important strategy for its prevention. This community service activity aimed to enhance students’ understanding of early marriage and its negative consequences. The activity was conducted using lectures, discussions, and question-and-answer sessions, supported by digital comic media and pocket books, in August 2025. The participants were 50 tenth- and eleventh-grade students of SMA Negeri 8 Muara Jambi who attended the socialization session in a single main room. The evaluation results showed a significant increase in knowledge, with the mean score rising from 4.5 before the intervention to 7.6 after the intervention, indicating an average increase of 3.1 points.These findings demonstrate that educational interventions using digital comics and pocket books are effective in improving students’ knowledge about early marriage and its consequences. Support from school principals and guidance and counseling teachers is expected to further strengthen efforts to prevent early marriage in the school setting